Difference In Pain Scale When Installation Infusion In Children Given And Not Distracted Techniques - Fatmawati; Asmirati (Jurnal Life Birth, 2019)
A hospital is a place where children often experience painful and unexpected medical procedures such as infusion that cause situational stress and anxiety that lead to unpleasant experiences for children. To reduce the pain, it is better to do non-pharmacological measures such as distraction technique. To find out the difference in pain scale when placing infusion in children who are given and not given distraction techniques in the emergency room of the Sultan Daeng Radja Hospital, Bulukumba Regency. This type of research is quantitative research, type This study used a quasi-experimental study with a non-randomized research design with control group design. The sample of this study were 36 children, divided into 2 groups, where the intervention group was 18 children, and the control group was 18 children. taken by a consecutive sampling method. Analysis of the data in this study used the statistical test of the Mann-Whitney test. Based on the pain scale when placing infusion in children in the group that was not given distraction (storytelling) techniques, there was the most in the category of very severe pain as many as 8 children (44.4%), while the group of children who were given distraction technique (storytelling) the most found in the category of moderate pain and severe pain as many as 5 children (27.8%). Based on the results of the analysis using the Mann-Whitney test, a significance value of 0.023 (p <0.05) was obtained. There is a difference in the scale of pain when placing infusion in children who are given distraction techniques (storytelling) with children who are not given distraction techniques (storytelling) in the emergency room of H. A. Sultan Daeng Radja Hospital in Bulukumba Regency.